Occurrence of 97 Pharmaceuticals in Wastewater and Receiving Waters: Analytical Validation and Treatment Influence - Paula Paíga; Sónia Figueiredo; Manuela Correia; Magda André; Roberto Barbosa; Sandra Jorge; Cristina Delerue-Matos (Journal of Xenobiotics, 2025)
This study analyzed 97 pharmaceuticals in samples of surface water, as well as influent and effluent from various wastewater treatment plants (WWTPs), during winter 2022 and spring 2023. Approximately 40% of the tested compounds were detected, at amounts ranging from below the methods’ detection limits to 5623 ng/L (2-hydroxyibuprofen in surface water) and 12,664 ng/L (caffeine in wastewater). Twelve compounds (acetaminophen, ampicillin, azithromycin, caffeine, fluoxetine, gemfibrozil, 2-hydroxyibuprofen, ibuprofen, ketoprofen, mazindol, naproxen, and salicylic acid) were detected with a 100% frequency in both surface water and wastewater samples. The observed high detection frequency of pharmaceuticals within the nonsteroidal anti-inflammatory drugs/analgesics, antibiotics, and psychiatric drug classes aligns with their high consumption. Caffeine was both the compound with the highest concentration and the most prevalent compound detected. Seasonal differences were observed, with higher concentrations detected during winter. Six of the eleven targeted metabolites and degradation products were detected in at least one sample. Risk quotient assessment revealed potential ecological risks, particularly for atorvastatin, caffeine, carbamazepine, and venlafaxine, exceeding risk thresholds for various trophic levels. The studied WWTPs showed limited removal efficiencies, with some compounds presenting higher concentrations in effluent than in influent, emphasizing the need for enhanced treatment to mitigate micropollutant risks.